Experimental studies on the liquid thermal conductivity of three saturated fatty acid methyl esters components of biodiesel. (October 2018) - Fan, Jing; Zhu, Zixuan; Wang, Xiaopo; Song, Fenhong; Zhang, Lihui
Highlights: Measurement of thermal conductivity of three saturated fatty acid methyl esters components of biodiesel was carried out. Thermal conductivity values of methyl myristate, methyl laurate and methyl caprate in liquid phase are reported for the first time. Based on the experimental data, a fitting correlation of temperature by using a quadratic polynomial function was proposed. Abstract: One of the attempts to reduce the consumption of fossil fuels is to replace them with renewable and clean fuels. Among these fuels, biodiesel has been considered as a promising alternative to petroleum diesel fuel. Thermal conductivity of biodiesel is a very important thermophysical property for its applications. In this work, the liquid thermal conductivity of three saturated fatty acid methyl esters (methyl myristate, methyl laurate and methyl caprate), usually the significant biodiesel components, was measured with the temperature ranging within (304–402) K, (283–402) K, (267–400) K, respectively. The total standard uncertainty of the experimental results was estimated to be less than 2% and the repeatability was better than ± 0.5%. The thermal conductivity data of each substance were fitted as a function of temperature, and the average absolute relative deviation and maximum absolute relative deviation between the experimental data and calculated results were 0.13% and 0.44% for methyl myristate, 0.21% and 0.53% for methyl laurate, 0.28% and 0.80% for methyl caprate, respectively.